(untitled) (Research, Society and Development, 2021)
Objective: to report the actions developed by the professional dental surgeon in coping with the pandemic of COVID-19, in the context of the Family Health Strategy (FHS). Method: this is an experience report about the strategies of action of the dental surgeon linked to the FHS, allocated in a municipality in the interior of Bahia, during the confrontation of the pandemic of COVID-19 in the period from March 2020 to March 2021 Results: it was evidenced that many practices were developed by dentists as an aid in sanitary health barriers, monitoring of patients by telemonitoring, production of materials for health education in addition to urgent and emergency care. Conclusion: the dentist can and has contributed to Primary Health Care (PHC) in several ways over the past few years and it was no different at this time of pandemic. After the report, it is clear that these professionals have added and contributed to the promotion, prevention and recovery of the population’s health.